Enhancing the Development of Infants and Toddlers with Dual Diagnosis of Autism Spectrum Disorder and Deafness - Thompson, Nanette; Yoshinaga-Itano, Christine (Seminars in Speech and Language, 2014)
Children diagnosed with autism spectrum disorder (ASD) are often referred for audiological diagnostic evaluation. This article provides some strategies for preparing children for a successful diagnostic evaluation. Children who are deaf or hard of hearing with a dual diagnosis of ASD may have difficulty learning to demonstrate detection or imitation of the Ling 6 sounds. The Ling 6 sounds are used to determine what a child with a dual diagnosis can hear and discriminate with amplification (hearing aids or cochlear implants). Because children with ASD may not look at the conversational partner and may have difficulty with imitation, adaptive strategies may be necessary to teach these children with dual diagnosis their first words. Strategies for teaching children with dual diagnosis through sign language will also be discussed.
Keywords: Autism; deaf; hard of hearing; early intervention; auditory; sign language